High Titers of Chlamydia trachomatis Antibodies in Brazilian Women with Tubal Occlusion or Previous Ectopic Pregnancy - A. C. S. Machado; E. M. B. Guimarães; E. Sakurai; F. C. R. Fioravante; W. N. Amaral; M. F. C. Alves (Hindawi Limited, 2007)
Objective. To evaluate serum chlamydia antibody titers (CATs) in tubal occlusion or previous ectopic pregnancy and the associated risk factors. Methods. The study population consisted of 55 women wih tubal damage and 55 parous women. CAT was measured using the whole-cell inclusion immunofluorescence test and cervical chlamydial DNA detected by PCR. Odds ratios were calculated to assess variables associated with C. trachomatis infection. Results. The prevalence of chlamydial antibodies and antibody titers in women with tubal occlusion or previous ectopic pregnancy was significantly higher (P<.01) than in parous women. Stepwise logistic regression analysis showed that chlamydia IgG antibodies were associated with tubal damage and with a larger number of lifetime sexual partners. Conclusions. Chlamydia antibody titers were associated with tubal occlusion, prior ectopic pregnancy, and with sexual behavior, suggesting that a chlamydia infection was the major contributor to the tubal damage in these women.